Implementasi Algoritme Extreme Learning Machine (ELM) Untuk Klasifikasi Penanganan Human Papilloma Virus (HPV) - Stefanus Bayu Waskito; Imam Cholissodin; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Human Papilloma is a virus that cause warts ilness. There are several treatment methods, but Immunotherapy and Cryotherapy are considered to be the best method to treat this ilness. However, none of them can heal all patients. Therefore, research to determine which method more appropriate for a certain patient is required. This research use Extreme Learning Machine Algorithm to help classify which method are better for certain patient. A tests is conducted to determine the effects of activation function, number of hidden neuron and and data ratio toward classification accuracy. It was observed that using Binary Sigmoid activation function, 80 testing data to 20 training data ratio, and 10 hidden neuron, the classification accuraccy reach 70,8%. And the classification time spent were relatively fast that is only 0.043 seconds.